2021
DOI: 10.1038/s41420-021-00424-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation of BAG co-chaperones by HIV-1 viral proteins and H2O2: implications for HIV-associated neurological disorders

Abstract: Despite increasing numbers of aged individuals living with HIV, the mechanisms underlying HIV-associated neurological disorders (HANDs) remain elusive. As HIV-1 pathogenesis and aging are characterized by oxidative stress as well as altered protein quality control (PQC), reactive oxygen species (ROS) themselves might constitute a molecular mediator of neuronal PQC by modulating BCL-2 associated athanogene (BAG) family members. Present results reveal H2O2 replicated and exacerbated a reduction in neuronal BAG3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…NeuroHIV remains highly prevalent among the HIVinfected population, yet its exact cause evades full understanding with no effective therapeutics available. HIV infection of astrocytes and subsequent dysregulation of astrocyte function are known to contribute to the disease [40,[68][69][70]. With GFAP being a major astrocytic protein involved in maintaining physiological homeostasis of astrocytes, we chose to determine if and how Nef might influence GFAP expression, possibly leading to astrocyte dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…NeuroHIV remains highly prevalent among the HIVinfected population, yet its exact cause evades full understanding with no effective therapeutics available. HIV infection of astrocytes and subsequent dysregulation of astrocyte function are known to contribute to the disease [40,[68][69][70]. With GFAP being a major astrocytic protein involved in maintaining physiological homeostasis of astrocytes, we chose to determine if and how Nef might influence GFAP expression, possibly leading to astrocyte dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, among all the members of the family, BAG5 has drawn considerable attention as it is expressed in the cardiomyocytes ( Gupta et al, 2016 ) and plays a pivotal role in monitoring cell homeostasis under stressful conditions ( Gupta et al, 2016 ; Duggan et al, 2021 ). In fact, studies have indicated that BAG5 protein overexpression can limit oxidative stress and mitochondrial dysfunction in the cells ( Wang et al, 2014 ; Gupta et al, 2016 ).…”
Section: Bag Protein Family and Its Molecular Interaction With Hsp70 ...mentioning
confidence: 99%
“…The role of BAG5 as a stress regulator is further substantiated by a very recent study which revealed that exposure of primary neuronal cultures to H 2 O 2 for 6 h induced oxidative stress. Also, this was accompanied by a reduction in the expression of BAG5 protein ( Duggan et al, 2021 ). This indicates that stressful conditions downregulate BAG5 expression and induce cell death.…”
Section: Role Of Bag5 In Regulating Endoplasmic Reticulum Stress and ...mentioning
confidence: 99%